‘Insane with courage’: free university experiments and the struggle for higher education in historical perspective - Amsler, Sarah (Berghahn Journals, 2017)
This article considers the role of experiments in learning in movements to democratise higher education ‘under the rule of capital’ (Gutierrez, Navarro and Linsalata 2017). It focuses on the emergence of a new generation of ‘free universities’ in the United Kingdom, situating these in a historical tradition of educational experimentation and a current context of global movements for autonomy from the state, capital and dominating epistemologies. It argues that free universities can contribute to transforming the relationship between knowledge, university and society, but that these contributions are often invisible within the logic of the dominant institutional systems. Conceptualising the projects as struggles for autonomy renders these contributions visible and valuable for educational reformers working both within and independently of the university.